EFEKTIVITAS PEMBELAJARAN GERAK DASAR KAYANG DENGAN BANTUAN TEMAN, DINDING DAN GYMBALL PADA SISWA KELAS IV SD NEGERI 5 SUMBEREJO KEMILING - Bahri, Saiful (Lentera: Jurnal Ilmiah Kependidikan, 2015)
This research aims to improve and enhance learning basic motion Kayang in class V in SD Negeri 5 Sumberrejo 2013/2014 school year, with the help of a friend, a support wall and assistance gymball.This type of research is classroom action research (Classroom Action Research) using three cycles. While the research subjects are students of class IV which amounts to 26 students, consisting of 16 men and 10 women. The data collection techniques with basic motion assessment scale observation Kayang.The results showed: that the first appraisal cycle with the use of methods of learning basic movement Kayang assisted with friends gained mastery learning success percentage 26.92%, while 44.93% effectiveness rate means the action has not been effective. In the second cycle of the basic motion Kayang learning methods with the help of the wall acquired mastery learning success percentage 46.16%, while 49.80% effectiveness rate means the action has not been effective. In the third cycle with the basic motion Kayang learning methods with the aid of gymball gained mastery learning success percentage 84.61%, with 78.07% effectiveness rate calculation. From the results of this study concluded that the learning material in particular floor gymnastics basic movements Kayang with tools to improve and enhance the basic motion Kayang the fourth grade students of SD Negeri 5 Sumberejo Kemiling.